Carnosine alleviates oxidative stress to prevent cellular senescence by regulating Nrf2/HO-1 pathway: a promising anti-aging strategy for oral mucosa - He, Haoan; Lv, Chao; Xie, Yuhong; Li, Wei; Ling, Zihang; Cheng, Bin; Tao, Xiaoan (Frontiers in Pharmacology, 2025)
Introduction: Aging is associated with significant metabolic alterations that contribute to cellular senescence and age-related functional decline. As individuals age, an increased prevalence of oral diseases and a gradual decline in oral functions are observed. However, the metabolic shifts underlying oral mucosal aging remain unexplored.Methods: We initially conducted histological analyses on the tongues from young (4-week-old), adult (4-month-old) and old (20-month-old) C57BL/6 mice to identify age-related alterations in the tongue mucosa. Subsequently, metabolomics analysis was performed to characterize metabolic profiles of mouse tongues across these age groups and identify metabolic biomarkers of oral mucosal aging. Then we validate the anti-senescence effect of carnosine and investigate its underlying mechanisms using a tert-butyl hydroperoxide (tBHP)-induced cellular senescence model in vitro. Finally, metabolomics analyses of human saliva and blood were conducted to explore associations between carnosine levels and systemic aging.Results: Compared to young and adult mice, we observed epithelial atrophy and an accumulation of senescent cells in the tongue mucosa of old mice. After that, we found significant differences in the metabolic profiles among the young, adult, and old mouse tongues. Carnosine was identified as a potential biomarker of oral mucosal aging, as its levels declined significantly with age. Consistently, carnosine synthase 1 (CARNS1) activity decreased, and carnosinase 2 (CNDP2) activity increased with age in the tongue mucosa. Furthermore, carnosine protected oral epithelial cells from tBHP-induced cellular senescence by reducing oxidative stress, mitigating DNA damage, and downregulating Nrf2/HO-1 pathway. In humans, salivary and blood carnosine levels also declined with age and were significantly associated with age-related diseases.Discussion: Our findings reveal dynamic metabolic reprogramming during natural oral mucosal aging and highlight the dual role of carnosine as both an aging biomarker and a therapeutic target for combating age-related mucosal degeneration. These insights support the development of novel carnosine-based interventions to preserve oral mucosal function, prevent age-related oral diseases, and improve oral health in the aging population, thereby advancing healthy aging.